PsycEXTRA Dataset 1991
DOI: 10.1037/e426892008-001
|View full text |Cite
|
Sign up to set email alerts
|

ACT research report series: Predicting college grades from ACT assessment scores and high school course work and grade information

Abstract: This study examined the accuracy of predictions of English, mathematics, social studies, and natural sciences course grades, and of overall freshman GPA. The predictions were based on ACT Assessment test scores and on high school course work and grade information from the ACT Assessment Course Grade Information Section (CGIS). Estimates of prediction accuracy were compared to those obtained using ACT scores and the four self-reported grades from the registration folder (TH index), ACT Assessment scores alone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…An ACT score of 30 is roughly equivalent to an SAT composite score of 1320-1350, and an ACT score of 25 roughly translates to an SAT composite score of 1130-1160. ACT scores have been validated as reliable predictors of future college performance (Noble, 1991) and college class placement in the subjects tested in the ACT (Ang & Noble, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ACT score of 30 is roughly equivalent to an SAT composite score of 1320-1350, and an ACT score of 25 roughly translates to an SAT composite score of 1130-1160. ACT scores have been validated as reliable predictors of future college performance (Noble, 1991) and college class placement in the subjects tested in the ACT (Ang & Noble, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Test takers are required to answer multiple-choice questions about both specific sections of the prose passage and the passage as a whole (see wwwactstudent.org/testprep/descriptions/ engdescript.html for more information). Both subcomponents have been validated against a standard measure of reading comprehension, the Nelson-Denny test (Noble, 1988;Stiggins, Schmeiser, & Ferguson, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…And non-cognitive measures are related to psychological factors, like social support and academic related skills. Some researchers showed the importance of traditional predictors for academic success (Noble, 1991;Reason, Terenzini & Domingo, 2006). Others emphasized on non-cognitive factors to adequately predict which students will succeed or fail in university (Tracey & Sedlacek, 1984;White & Sedlacek, 1986).…”
Section: Prediction Of College Gpamentioning
confidence: 99%
“…Noble (1991) found that the use of just one factor alone to determine academic success was not as efficient as using both high school grades and ACT scores. Cohn, et.…”
Section: Background and Statement Of The Problemmentioning
confidence: 99%
“…Julie Noble (1991) studied how ACT scores and high school grades predicted college success. The data consisted of a student's ACT scores in English, Mathematics, Social Studies, Natural Sciences, and the ACT composite score.…”
Section: Chapter II Literature Reviewmentioning
confidence: 99%